Studi Pasal 53 KHI Dalam Perspektif MUI Jepara - Asep Rojudin (Isti`dal : Jurnal Studi Hukum Islam, 2020)
An analysis of article 53:pregnant marriages is reviewed by the Indonesian Ulama Council (MUI).   Syariah and Law faculty of Nahdlatul Ulama Islamic University (UNISNU) Jepara. This study aims to determine the correlation between the Compilation of Islamic Law (KHI) of the Indonesian Ulama Council and how the views of the Indonesian Ulama Council (MUI) on article 53 KHI (marrying pregnant). This research includes into qualitative research. In analyzing this research, the author uses a juridical-normative method that is research on the principles of law carried out on legal norms which are the standards for behaving or doing appropriate deeds. The Indonesian Ulama Council, which has an important role and authority in arguing or giving legal opinions in the midst of society and its used as an influential consideration for the Islamic community, especially Jepara Regency, has a lot of marriage dispensations in the Jepara District Religion Court for various reasons, but one of them is the occurrence of pregnant marriages (pregnancy outside marriage) in Jepara district. So the writter intends to conduct an analysis of article 53 of the Compilation of Islamic Law which will be reviewed from the views of the Indonesian Ulama Council, especially in Jepara district. The Compilation of Islamic Law has been regulated, as a consideration of marriage dispensation which until now has been made a decision and an alternative to save the family's good and efforts to keep a child from being pregnant as a result. With Article 53 KHI and the opinion of the Jepara Regency MUI which has been written in the contents of a scientific work which consists of the correlation between KHI and MUI in establishing a law, and the MUI's view of article 53 KHI which discusses marriage intermarriage with the scope of Jepara district. Based on this research it can be concluded that pregnancy marriage in this thesis provides the view that the MUI explained: pregnant marriages should be legally married as soon as possible and written legally in KUA with men who doing the sex out of marriage with a duration of time before 6 months pregnancy, so the child gas a nasab from his father. Analisis pasal 53 KHI tentang kawin hamil di tinjau dari Majelis Ulama Indonesia (MUI). Fakultas Syariah dan Hukum UniversitasIslam Nahdlatul Ulama (UNISNU) Jepara. Penelitian ini bertujuanuntuk mengetahui korelasi antara Kompilasi Hukum Islam (KHI) Majelis Ulama Indonesia  dan  bagaimana pandangan  Majelis Ulama  Indonesia  (MUI) tentang KHI pasal 53 (kawin hamil). Penelitian ini termasuk Penelitian kualitatif. Dalam menganalisis penelitian ini, penulis menggunakan metode yuridis-normatif yaitu penelitian  terhadap  asas-asas  hukum  dilakukan  terhadap norma-norma  hukum yaitu yang merupakan patokan-patokan untuk bertingkah laku atau melakukan perbuatan yang pantas. Majelis Ulama Indonesia yang memiliki peran penting dan wewenang dalam berpendapat atau memberikan opini hukum di tengah-tengah masyarakat dan dijadikan suatu pertimbangan yang berpengaruh bagi masyarakat Islam khususnya Kabupaten Jepara, banyak sekali dispensasi nikah di Pengadilan Agama Kabupaten Jepara dengan berbagai alasan, namun salah satunya karena terjadinya kawin hamil (hamil di luar nikah) di kabupaten Jepara. Maka penulis bermaksud melakukan analisis terhadap pasal 53 Kompilasi Hukum Islam yang akan di tinjau dari pandangan Majelis Ulama Indonesia khususnya di kabupaten Jepara. Kompilasi Hukum Islam telah mengatur, sebagai pertimbangan dispensasi nikah yang  sampai   saat   ini   dijadikan   keputusan dan   alternatif   untuk menyelamatkan nama baik keluarga maupun upaya dalam menjaga nasab seorang anak hasil dari kawin hamil. Dengan pasal 53 KHI dan pendapat MUI kabupaten Jepara yang telah ditulis di dalam isi karya ilmiah yang terdiri dari korelasi KHI dengan MUI dalam menetapkan suatu hukum, dan pandangan MUI mengenai pasal 53 KHI yang membahas tentang kawin hamil dengan ruang lingkup wilayah kabupaten Jepara. Berdasarkan penelitian ini dapat diambil kesimpulan bahwasanya Kawin hamil pada skripsi ini memberikan pandangan bahwa MUI mejelaskan: kawin hamil harus sesegera mungkin dinikahkan secara sah dan tercatat di KUA dengan pria yang menghamilinya dengan durasi waktu sesbelum 6 bulan di dalam kandungan agar anak tersebut memiliki nasab dari ayahnya.